2020
DOI: 10.1017/s0017816020000036
|View full text |Cite
|
Sign up to set email alerts
|

Fable and Fact: Judging the Language of Scripture (Judges 9:8–15) from Antiquity to Modernity

Abstract: In the movement of scriptural interpretation from antiquity to the modern period, critical attention in the Christian world recurrently turns to a provocative passage in the book of Judges. The passage (Judg 9:8–15) is a story about talking trees, a tale that is repeatedly called a “fable” (fabula) by Christian interpreters. In seeking from varying perspectives to explain the role of a fabulous dialogue in the discourse of truth, such interpreters suggest pressing issues in the assessment of figurative languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…117 Not long ago, in the opening decade of the twenty-first century, an article appeared that included an extended investigation of the botanical identity of that "bramble"-Hebrew aṭad ‫‪)-in‬אטד(‬ the fable of Jotham. 118 The author concluded that the aṭad was quite possibly what is called by botanists Ziziphus spina-christi-that is, in an expression conspicuously highlighted in the article in a bold font, "Christ Thorn." 119 "Its scientific name," the author continued, "comes from the perception commonly accepted among scholars that its thorns make the tree the most plausible candidate for the plant of which Jesus' crown was made."…”
Section: Density and Diversitymentioning
confidence: 99%
“…117 Not long ago, in the opening decade of the twenty-first century, an article appeared that included an extended investigation of the botanical identity of that "bramble"-Hebrew aṭad ‫‪)-in‬אטד(‬ the fable of Jotham. 118 The author concluded that the aṭad was quite possibly what is called by botanists Ziziphus spina-christi-that is, in an expression conspicuously highlighted in the article in a bold font, "Christ Thorn." 119 "Its scientific name," the author continued, "comes from the perception commonly accepted among scholars that its thorns make the tree the most plausible candidate for the plant of which Jesus' crown was made."…”
Section: Density and Diversitymentioning
confidence: 99%